Prefrontal serotonin depletion delays reversal learning and increases theta synchronization of the infralimbic-prelimbic-orbitofrontal prefrontal cortex circuit - Estrada-Reyes, Yoana; Cervantes-Alfaro, José Miguel; López-Vázquez, Miguel Ángel; Olvera-Cortés, María Esther (Frontiers in Pharmacology, 2024)
Introduction Prefrontal serotonin plays a role in the expression of flexible behavior during reversal learning tasks as its depletion delays reversal learning. However, the mechanisms by which serotonin modulates the prefrontal cortex functions during reversal learning remain unclear. Nevertheless, serotonin has been shown to modulate theta activity during spatial learning and memory. Methods We evaluated the effects of prefrontal serotonin depletion on theta activity in the prefrontal infralimbic, prelimbic, and orbitofrontal (IL, PL, and OFC) subregions of male rats during a spatial reversal learning task in an aquatic T-maze. Results Prefrontal serotonin depletion delayed spatial reversal learning and increased theta activity power in the PL and OFC. Furthermore, animals with serotonin depletion had increased functional coupling between the OFC and the IL and PL cortices compared with the control group. Discussion These results indicate that serotonin regulates reversal learning through modulation of prefrontal theta activity by tuning both the power and functional synchronization of the prefrontal subregions.